Effect of drinking water temperature on water intake, feed intake and milk production of crossbred dairy cattle at high altitude temperate Himalayas - GOLHER, D M; THIRUMURUGAN, P; PATEL, B H M; UPADHYAY, V K (The Indian Journal of Animal Sciences, 2014)
A study was conducted to explore the utility of different drinking water temperature, viz. ambient water temperature (10.25±0.28°C, T1), 15–20°C (T2) and 35–40°C (T3) during winter at IVRI, Mukteshwar campus on 18 crossbred (HF × Haryana) lactating cows. They were divided into 3 groups of 6 each and various parameters were studied. At open environment maximum temperature, minimum temperature and mean relative humidity were 11.81±0.45, 1.52±0.27°C and 57.43±2.79%, respectively, the corresponding values for microclimate were 16.61±0.36, 6.68±0.61°C and 86.75±0.55%. Average water intake per cow per day was significantly higher in T3 (40.66±0.55) and compared with cows in T1 (38.63±0.42) and T2 (37.53±0.47). Dry matter intake was more for cows in T3. Daily mean milk yield for the cows in T3 (7.56±0.18 litre) was significantly higher than T1 (6.95±0.16 litre) and T2 (7.06±0.17 litre). Milk SNF, protein and total solids percentages were significantly higher for cows consuming warm drinking water in T2 (15–20°C) and in T3 (35–40°C) than cows consumed ambient cool drinking water. Cows in warm drinking water groups showed relatively more gain in body weight compared to cows provided with ambient cool drinking water. It was concluded that the crossbred cows consuming warm water (35–40°C) performed better than the cows consuming comparatively cold water.